Association between Covid-19 and Diabetes Mellitus - Bushra Aslam, Basit Naeem, Sadia Aman, Mutayyaba Majeed (Pakistan Journal of Medical & Health Sciences, 2023)
Aim: To determine the association between Covid-19 and diabetes mellitus. Study Design: Retrospective study. Place and Duration of Study: Department of Medicine & Respiratory Physiology, Independent Medical College Faisalabad from 1st July 2022 to 31st December 2022. Methodology: Fifty five patients received at outdoor patient department of Independent University Hospital with confirmed diagnosis for Covid-19 through naso-pharyngeal reverse transcription polymerase chain reaction (RT-PCR) and aged 13-65 years were included. The complete medical files of each confirmed Covid-19 case was completely studied in relevance to diabetes mellitus association and compared with normal matched controls that only visited the OPD against the suspicion of the disease and underwent complete biochemical profiling. The baseline levels of HbA1C and glucose monitoring in each patient and control was done and compared. Results: The mean age of the CoVid-19 cases was 39.5±5.3 years while of controls as 25.65±4.3 years. There was an obvious significant variance in the odds ratio of Covid-19 patients and those of controls in reference to diabetes mellitus. A significant increase was observed in Odds Ratio of Covid-19 cases within the age group of 51-65 years. The Elixhauser Comorbidity Index (ECI) categories also presented, ECI >5 to be higher in Covid-19 cases than controls. Conclusion: There is a higher risk of diabetes new onset in Covid-19 confirmed cases as compared to matched controls. Key words: Covid-19, Incidence, Alarming, Diabetes, Socioeconomic